Experimental Study on Physico-Chemical Parameters of Ground Water at Peth Seer Sopore J&K (International Journal of Innovative Research in Engineering & Management, 2022)
Human activities, use of fertilizers and  chemicals in agricultural fields are the main causes of  ground water contamination. Therefore to protect and  improve the natural eco system, water quality analysis is  essential. The main goal of this work is to study the criteria  governing the groundwater quality in the nearby wells of  Peth Seer, Sopore J&K. Total 12 groundwater samples and  15 water quality parameters for each sample are considered  in this study. The ground water samples of all the selected  stations were collected for a physiochemical analysis. For  calculating present water quality status, following 16  parameters have been considered Viz. pH, TDS, EC,  Chloride concentration, Nitrate concentration, Sulphate  concentration, Alkalinity, Fluoride concentration, Total  hardness, Magnesium, Calcium, Sodium, Potassium,  Temperature, Turbidity, Residual chlorine. The obtained  results are compared with WHO (2017). The study reveals  that the concentrations of all the constituents are well  within the permissible limits of WHO (2017). Groundwater  in the study area is suitable for drinking purpose as  prescribed by WHO (2017) and irrigation purposes as  prescribed by IS-11624(1986).
Keywords: TDS (Total Dissolved Solids); EC (Electrical Conductivity); WHO (World Health Organization); Turbidity